Penerapan Model Flipped-Classroom untuk Meningkatkan Performa Guru pada Pelajaran Bahasa Inggris (Studi Kasus di SMA Negeri 1 Narmada, Nusa Tenggara Barat) - Manikowati Manikowati (Universitas Sebelas Maret, 2019)
Learning time reduction in SMA N 1 Narmada as an earthquake effect became thebackground of flipped-classroom implementation. The research is to: 1) analyze teacher’s preparation in implementing a flipped-classroom; 2) analyze teacher’s performance in it; 3) analyze the uses of multi media in it; and 4) suggest or recommend to enhance it. The research used qualitative method by studying teacher’s lesson plan, observing the implementation, and interviewing the teacher and the headmaster. To gain the data, the researcher used instruments like the teacher’s lesson plan, the observation and interview sheets. From the investigation, the researcher concluded that: 1) the teacher was capable of preparing his teaching and learning activities, the flipped-classroom implementation was implicitly stated in his plan; 2) the teacher’s performance in the process was enhanced. He could optimize the student’s learning; 3) multi media used, video graphics dan powerpointcould be applied well; and 4) suggestion was given to the teacher to improve his teaching performance, including to learn more about the learning models. For the headmaster it was suggested to control the teachers’ performance and conduct a teacher-parent program. Meanwhile, for BPMPK it was to be a good school-partner, especially in case of innovative learning models